Assessment of the application of double-modified nasopharyngeal airways versus the use of low-flow nasal cannula during pediatric upper gastrointestinal endoscopy: A prospective, randomized, noninferiority, controlled trial - Mostafa M. Hussein; Akram M. Amer; Mohammed M. Maarouf (Journal of Anaesthesiology Clinical Pharmacology)
Background and Aims: Pediatric upper gastrointestinal (GI) endoscopy is commonly performed under deep sedation, which is frequently associated with respiratory complications. The study compared the respiratory benefits of applying bilateral modified nasopharyngeal airways (NPAs) to conventional low-flow nasal cannula (LFNC). Material and Methods: Fifty patients scheduled for an upper GI endoscopy under deep sedation, with an American Society of Anesthesiologists physical status I/II, were enrolled in the study. The patients were randomly divided into bilateral NPA group and the LFNC group. Fentanyl and propofol were administered to both groups to maintain deep sedation. After the application of NPA or LFNC, the hypoxic incidents (oxygen saturation [SpO2] <90%) and airway interventions during the procedure were noted and recorded. Other outcomes such as nasopharyngeal injuries, gastroenterologist satisfaction, the incidence of hypotension or bradycardia, and postoperative nausea and vomiting were also compared. Results: No significant differences were noted in the demographic data. The incidence of hypoxemia was 16% (n = 4) in the NPA group versus 36% (n = 9) in the LFNC group (P = 0.634). Airway intervention was lower in the NPA group compared to the LFNC group, but the difference was not significant (P = 0.539). No significant differences were noted in the incidence of nasopharyngeal injuries, postoperative nausea and vomiting, bradycardia, and hypotension. The NPA group showed higher gastroenterologist’s satisfaction (P = 0.003). Conclusion: Double-modified NPA in pediatric endoscopy was noninferior to the standard LFNC for the incidence of hypoxemia and airway intervention rate, with greater gastroenterologist satisfaction.